The development of culturally responsive pedagogy in traditional crafts ceramic for secondary school / Noor Hasmida Mohd Khair - Mohd Khair, Noor Hasmida (2015)
This research urged to integrate a multicultural education into Visual Art Education curriculum because of its limit especially in craft component which focus only on Malay handcraft and certain ethnical group. Thus, this study aimed to develop a Culturally Responsive Pedagogy In Traditional Crafts Ceramic For Secondary School to promote a module that developed by Siti Zuraida Maaruf (2014). It will include each element from Malays, Chinese and Indian culture and use a Developmental Research Design that consists of three phase. In Phase 1: Analysis Need, it involves a collective data from semi structure interview done by 5 lecturers that well-experienced in designing ceramic material. In Phase 2: Design and Development, Two Round Delphi Technique done by 10 panelist of experts to recognize the suggestion of instructional material in each races. Researcher has chosen technique component and teaching method, technique equipment and teaching material and also the activity component from the module developed by Siti Zuraida Maaruf (2014). Research development of this module consists of Text module, Interactive Power Point Presentation and Daily Lesson Plan for VAE teachers. In Phase 3: Implementation and Evaluation, is the final process where the data valued from semi structure interview based on teachers perspective and students experience. Based on the findings shown that implementation of the module is relevant. Student can learn excitingly about other culture, gain unity and harmony. It is hoped to have a culturally responsive pedagogy module in traditional ceramic crafts for secondary school that include ceramic from Sabah and Sarawak.